Manipulative aspects of sensationalism in journalistic text (Herald of Journalism, 2023)
The article deals with the problem of sensationalism in journalistic texts as a kind of manipulation of the public consciousness. It is noted that in the modern period, due to the huge volumes of information consumption, various media platforms, as well as television analytical and leisure programs are in fierce competition with each other. The priority of the activity of journalists is the necessary rating, therefore, more and more information materials contain a sensation.The aim of the article is to study the phenomenon of sensation as a manipulative technique used by journalists to promote certain ideas. In addition to the moral and ethical aspect, in the modern period of information wars, sensation also becomes the propaganda tool. The scientific significance of the article consists in an attempt to differentiate the main techniques of sensational presentation of information and to offer tools for recognizing sensations in the context of manipulative approaches to the transmission of media content.The research methodology provides a systematic approach; method of comparative analysis is used. The result of the research is the identification of new media discourses in the modern period. If a journalist does not distinguish informational and sensational approaches to his/her messages, he/she risks getting into a situation where, instead of ensuring the information needs of society, he/she will commit unacceptable information offenses and even crimes. This aspect determines the scientific value of the article. The practical significance lies in the possibility of introducing the results of the research into teaching at journalism faculties in the disciplines: "Language and style of the media", "Legal foundations of journalism", "Political journalism", etc., as well as in advanced training courses for journalists.Keywords: journalism, sensation, journalistic text, mass media, television, manipulation, manipulative techniques.